Depressive personality vulnerability in chronic physical pain: Centrality of sociotropy. Issue 6 (5th January 2018) - Shahar, Golan; Lerman, Sheera F.; Topaz, Maayan; Brill, Silviu; Shalev, Hadar; Rudich, Zvia
Abstract: Objective: Chronic physical pain is one of modern medicine's principal challenges. Recently, there has been a keen research interest in the role of depressive personality vulnerability (DPV) in the course of chronic pain. This is the first attempt to examine the role of three leading DPV dimensions—sociotropy, autonomy, and self‐criticism—in chronic pain. Method: Chronic pain patients ( N = 428) were assessed four times as to their pain, disability, anxious depression, and pain‐based catastrophizing. At Time 1, sociotropy, autonomy, and self‐criticism were also assessed. The effects of sociotropy, autonomy, and self‐criticism on pain, disability, anxious depression, and pain‐based catastrophizing were examined using structural equation modeling analyses. Results: All DPV dimensions uniquely predicted Time 1, but not Time 2, anxious depression. Sociotropy predicted Time 1 pain and catastrophizing over and above anxious depression, as well as an increase in catastrophizing over time. Autonomy predicted a decrease in catastrophizing and disability, and Time 1 anxious depression predicted an increase in self‐criticism. Conclusions: Sociotropy appears to be a unique dimension of DPV in chronic pain.